High sensitivity X-ray analysis for a low accelerating voltage scanning electron microscope using a transition edge sensor. (26th May 2020) - Tanaka, Keiichi; Takano, Akira; Nagata, Atsushi; Nakayama, Satoshi; Takahashi, Kaname; Ajima, Masahiko; Obara, Kenji; Chinone, Kazuo
Abstract: A scanning electron microscope transition edge sensor has been developed to analyze the minor or trace constituents contained in a bulk sample and small particles on the sample under a low accelerating voltage (typically <3 keV). The low accelerating voltage enables to improve the spatial analysis resolution because the primary electron diffusion length is limited around the sample surface. The characteristic points of our transition edge sensor are 1) high-energy resolution at 7.2 eV@Al-Kα, 2) continuous operation by using a cryogen-free dilution refrigerator and 3) improvement of transmission efficiency at B-Kα by using thin X-ray film windows between the sample and detector (about 30 times better than our previous system). Our system could achieve a stabilization of the peak shift at Nd-Mα (978 eV) within 1 eV during an operation time of 27 000 s. The detection limits with B-Kα for detection times 600 and 27 000 s were 0.27 and 0.038 wt%, respectively. We investigated the peak separation ability by measuring the peak intensity ratio between the major constitute (silicon) and the minor constitute (tungsten) because the Si-Kα line differs from the W-Mα line by only 35 eV and a small W-Mα peak superimposed on the tail of the large Si-Kα peak. The peak intensity ratio (I(W-Mα)/I(Si-Kα)) was adjusted by the W particle area ratio compared with the Si substrate area. The transition edge sensor could clearly separate the Si-Kα and W-Mα lines even under a peak intensity ratio of 0.01.